Pengaruh Kepemimpinan Etis, Kompetensi Digital, Motivasi Kerja, dan Komitmen Organisasi terhadap Kesiapan SDM dalam Transformasi Polri Presisi - Dachi, Bahagia; Wijaya, Oscarius Yudhi Ari (Jurnal EMT KITA, 2026)
This study examines how ethical leadership, digital competence, work motivation, and organizational commitment influence human resource readiness in supporting the Polri Presisi transformation agenda. Using a literature review approach, this research synthesizes findings from national accredited journals and reputable international publications within the last decade. The review indicates that ethical leadership strengthens integrity, trust, and consistent behavioral standards among police personnel. Digital competence emerges as a crucial factor in adapting to technological advancements such as online policing systems, data-driven decision-making, and AI-based public service platforms. Work motivation positively contributes to readiness for change, especially when supported by a work environment that provides recognition, growth opportunities, and psychological empowerment. Organizational commitment further reinforces members’ willingness to participate and stay aligned with institutional transformation goals despite structural or technical challenges. Collectively, these four variables form an integrated foundation for shaping competent, adaptive, and accountable human resources within the Indonesian National Police. The findings offer valuable insights for enriching academic discussions and guiding strategic HR development policies to strengthen internal capacity for future transformations.